2012
DOI: 10.1007/s13204-012-0097-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nanosilver on egg quality traits in laying Japanese quail

Abstract: Silver nanoparticles could prove to be a valuable alternative raw material for antibiotics and disinfectants as it is relatively free of adverse effects. Nanosilver is now been put to practical use in commonly used items, such as, clothes, electric home appliances, and electronic industry, but has not been widely applied in the medical or pharmacological fields. This study was designed to investigate the effects of nanosilver on egg quality traits in laying Japanese quail in completely randomized design with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 13 publications
0
6
1
1
Order By: Relevance
“…For three days, there was a rapid decline Previous studies have shown that silver nanoparticles are absorbed and metabolized by soft tissues where they display toxic activity and produce macro-and/or microscopic changes [19,20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For three days, there was a rapid decline Previous studies have shown that silver nanoparticles are absorbed and metabolized by soft tissues where they display toxic activity and produce macro-and/or microscopic changes [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…In the work of Sawosz et al [6] and Fondevila et al [7] the application of silver nanoparticles is investigated as a likely alternative to feed additives for stimulating bird growth. A number of authors have emphasized that nanosilver is a disinfecting agent that is relatively safe for health [2,7,19]. However, its potential use in poultry production needs more thorough studies on its possible toxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are now used less in water and chicken feeds. However, according to two recent studies, the application of these compounds even on the mucosa can be absorbed and affect the chickens [30,31]. Finally, the current accumulation of silver ions in meat and other edible tissues of chickens supplied in Isfahan, is very minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Higher body weight gain rates in birds may be to less energy expenditure and better feed intake by the birds. The interaction among energy intake and expenditure significantly affects the overall performance of birds particularly body weight gain (Farzinpour et al, 2013). Overall body weight gain increases by modulating the light duration and consequently decreasing dark period for birds to improve intake It is evident that consequences of food activity depends upon the photoperiod.…”
Section: Effect Of Photoperiod and Light Intensity On Feed Intake Weight Gain And Feed Conversion Ratio Of Coturnix Japonicamentioning
confidence: 99%